Hearths in the coastal areas of northernmost Sweden, from the period AD 800 to 1950 - Liedgren, Lars; Bergman, Ingela; Ramqvist, Per H.; Hörnberg, Greger (Rangifer, 2016)
This paper presents a study of the chronological setting of hearths registered in FMIS (digital register containing records of all known ancient monuments in Sweden) in the provinces of Västerbotten and Norrbotten, Northern Sweden. A total of c. 1500 hearths are known in the area, mainly situated north of the river Skellefteälven. Within a study area of 107 x 94 km, 32 hearths were randomly selected for excavation, each site embracing 1-14 hearths. The sites were scanned using a metal detector and nearly all artifacts found were from the period AD 1600-1900. 14C-datings of charcoal and burned bones corroborated that most hearths were used during this period, with a large number dating to the 19th and 20th centuries. Many hearths contained bones from mature reindeer, indicating that the hearths were related to reindeer herding. We suggest that most hearths are related to nomadic Sami reindeer herders using coastal areas for winter pasture, possibly resulting from the breakdown of the “lappskatteland” (taxation lands) system and an increase in reindeer numbers.